Unveiling the Incidence of Interfirm Collaboration: Evidence from Research and Development Companies in Malaysia - Zurina Adnan; Johanim Johari; Hazman Shah Abdullah; Jasmine Ahmad (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
Nowadays, interfirm collaboration has become an increasingly popular strategy among many organizations in various industries, in order to remain competitive. Based on the contingency theory, this paper examines the moderating effect of interfirm collaboration on the relationship between Human Resource Management (HRM) practices and organizational performance. Interfirm collaboration refers to the collaboration strategies undertaken by R&D companies, with other companies in similar or diverse functional areas, including R&D, marketing, or manufacturing, to enhance performance. Using data from 64 R&D companies, the hierarchical regression analyses showed that only collaboration in R&D and functional collaboration in manufacturing significantly moderated the relationship between HRM practices and organizational performance. Overall, the results provided partial support in the domain of the contingency theory. These results, however, are limited by the small sample size, which might have produced non-significant findings. Therefore, the generalization should be taken cautiously. Future research with a larger sample size is needed to confirm the findings.